2016
DOI: 10.1016/j.juro.2015.10.182
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Optical Biopsy during Robotic Assisted Radical Prostatectomy Using Confocal Endomicroscopy

Abstract: Purpose Intraoperative optical biopsy technologies may aid identification of important anatomic landmarks and improve surgical outcomes of robotic-assisted radical prostatectomy (RARP).We sought to evaluate the feasibility of confocal laser endomicroscopy (CLE) during RARP. Materials and Methods Twenty-one patients with biopsy-proven prostate cancer scheduled for RARP were recruited. After intravenous administration of fluorescein, 15 patients underwent in vivo intraoperative CLE of prostatic and periprostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 31 publications
0
42
0
2
Order By: Relevance
“…Cellvizio© (Mauna Kea Technologies, Paris, France) the most commonly used CLE system, has been applied to urology both during endourological procedures for TCC and during RP. Cellvizio consists of fibre optic probes for image acquisition, with a more shallow tissue penetration, a lower cell resolution and a smaller field of view, when compared to FCM . However, it is worth mentioning that the NeuroSAFE and the Cellvizio were used to assess surgical margins, but in the present study random biopsies were taken from the prostate and the margins were not assessed, as our main aim was to initially assess the feasibility of FCM in prostatic tissue examination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cellvizio© (Mauna Kea Technologies, Paris, France) the most commonly used CLE system, has been applied to urology both during endourological procedures for TCC and during RP. Cellvizio consists of fibre optic probes for image acquisition, with a more shallow tissue penetration, a lower cell resolution and a smaller field of view, when compared to FCM . However, it is worth mentioning that the NeuroSAFE and the Cellvizio were used to assess surgical margins, but in the present study random biopsies were taken from the prostate and the margins were not assessed, as our main aim was to initially assess the feasibility of FCM in prostatic tissue examination.…”
Section: Discussionmentioning
confidence: 99%
“…The intraoperative integration of FCM analysis may offer many advantages to the management of patients with prostate cancer, with a real‐time simplified pathological analysis preparation and interpretation. Tissue management is extremely fast (<5 min) compared to VR‐SIM (4–5 min) , Cellvizio (10 min) , NeuroSAFE (35 min) , and MPM (<60 min) . Additionally, there are no fixation artefacts on the specimen and tissue integrity is maintained during FCM analyses, making the sample available for subsequent histopathological examination.…”
Section: Discussionmentioning
confidence: 99%
“…This technique uses blue light to detect an agent that was previously injected near the target site, a fluorescent derivative of which accumulates in damaged tissue. Other extensively employed techniques that take advantage of the fluorescent properties of tissues include confocal endomicroscopy—used to obtain optical biopsies of endoluminal surfaces (eg, in prostatectomy) with high spatial resolution—and fluorescence lifetime imaging, used for instance to detect polyps in the colon 96 97. Many promising results have also been achieved through 3D optical coherence tomography, a scanning method that allows to create depth maps of the tissue only using light and thus can be incorporated well in endoscopy;98 99 it can also perform high-resolution scans at the cellular level 91…”
Section: Imagingmentioning
confidence: 99%
“…The most commonly used fluorescent dye is fluorescein. CLE is under investigation for gastrointestinal, urothelial and pulmonary diseases, while for PCa so far, only one study on CLE is reported [14,[18][19][20]. Lopez et al performed CLE during robot-assisted laparoscopic prostatectomy (RALP) in 21 patients to investigate the ability of CLE to assess surgical margins and nerve tissue with promising CLE based characteristics of prostatic and periprostatic tissue [20].…”
mentioning
confidence: 99%